Dark matters : pessimism and the problem of suffering - Lugt, Mara van der, 1986- (Princeton University Press, 2021)
"An intellectual history of the philosophers who grappled with the problem of evil, and the case for why pessimism still holds moral value for us todayIn the seventeenth and eighteenth centuries, philosophers engaged in heated debates on the question of how God could have allowed evil and suffering in a creation that is supposedly good. Dark Matters traces how the competing philosophical traditions of optimism and pessimism arose from early modern debates about the problem of evil, and makes a compelling case for the rediscovery of pessimism as a source for compassion, consolation, and perhaps even hope.Bringing to life one of most vibrant eras in the history of philosophy, Mara van der Lugt discusses legendary figures such as Leibniz, Hume, Voltaire, Rousseau, Kant, and Schopenhauer. She also introduces readers to less familiar names, such as Bayle, King, La Mettrie, and Maupertuis. Van der Lugt describes how the earliest optimists and pessimists were deeply concerned with finding an answer to the question of the value of existence that does justice to the reality of human suffering, but how they were fundamentally divided over what such an answer should look like.A breathtaking work of intellectual history by one of today's leading scholars, Dark Matters reveals how the crucial moral aim of pessimism is to find a way of speaking about suffering that offers consolation and does justice to the fragility of life"--